2016
DOI: 10.19082/2057
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Outcomes, and Resolution of Conflicts in Marriage among Iranian women: A qualitative study

Abstract: IntroductionFamily’s conflict is the important determinant of the quality and quantity of relationships among family members. No study of which we are aware has assessed conflicts, especially among normal or apparently satisfied couples in the Iranian context. This study explored that how women deal with different points, ideas and behaviors in marital life.MethodsFor the study, we recruited 30 to 45-year-old housewives who visited health centers in Tehran, Iran. The participants (n = 45) were selected using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…To better understand this effect in-depth, we seem to understand two things, the behavioral correlates of marital discord, and the biological makeup of human beings. Previous research ndings showed that the causes of marital discord were related to behavioral di culties (33,34). Meanwhile, the treatments proposed in the current systematic review and meta-analysis included educational training.…”
Section: Discussionmentioning
confidence: 83%
“…To better understand this effect in-depth, we seem to understand two things, the behavioral correlates of marital discord, and the biological makeup of human beings. Previous research ndings showed that the causes of marital discord were related to behavioral di culties (33,34). Meanwhile, the treatments proposed in the current systematic review and meta-analysis included educational training.…”
Section: Discussionmentioning
confidence: 83%
“…Many researchers have identi ed inadequacy in effective communication and constructive con ict-solving as main barriers to couple communication, which consequently leads to reduced relationship satisfaction (18,19). Eliminating such barriers can improve the couple communication and their social interactions and increase the quality of life (20).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian tersebut memiliki kesesuaian dengan penelitian terdahulu yang dilakukan oleh (Kuncewicz, 2011), laki-laki cenderung melakukan resolusi aktif yaitu voice dan exit (t = -4.74), sementara perempuan lebih melakukan resolusi pasif yaitu neglect dan loyalty (t = 5.27). Bentuk perilaku pasif yang umumnya dilakukan Studi Komparasi Marital Conflict Response pada Pasangan Suami-Istri Di Kota Makassar (Ditinjau dari Model Exit, Voice, Loyalty, dan Neglect) perempuan sebagai resolusi atas konflik pernikahan adalah dengan menerima keadaan seperti, memberi respek kepada suami karena suami dianggap sebagai kepala keluarga, memberi perhatian kepada suami, mencintai pasangan, berada pada kontinum konstruktif, sementara pengabaian dan penghindaran pasangan seperti menghindari percakapan, merasa puas dengan diri sendiri tanpa adanya pasangan berada pada kontinum destruktif (Asadi et al, 2016). Disisi lain, responden laki-laki lebih cenderung terlaporkan melakukan resolusi konflik secara aktif, seperti berupaya mendiskusikan masalah, menyarankan untuk pergi berkonsultasi, yang berada pada kontinum tindakan konstruktif, sementara perilaku mendominasi dan memperbaiki keadaan dengan menggunakan power, seperti melakukan tindakan agresif, melakukan reaksi disertai kekerasan baik secara fisik ataupun verbal, dan berselisih, yang berada pada kontinum perilaku destruktif (Asadi et al, 2016).…”
Section: Tabel 4 Hasil Uji Independent Sample T-testunclassified